Investment Opportunity Set, Firm Growth, and Profitability on Firm Value: The Moderating Role of CSR in Indonesian Manufacturing Firms (JII) - Geodimas Wibowo; Dimas Pratomo; Citra Etika (Manunggal Halim Jaya, 2026)
This study investigates the effect of the Investment Opportunity Set (IOS), firm growth, and profitability on firm value, with Corporate Social Responsibility (CSR) as a moderating variable. The research focuses on manufacturing companies listed in the Jakarta Islamic Index (JII) for 2019–2024. IOS is measured using the Market to Book Value ratio, firm growth by changes in total assets, profitability by Return on Equity (ROE), firm value by Price to Book Value (PBV), and CSR by the Global Reporting Initiative (GRI) 2016 indicators. A total of six companies were selected through purposive sampling, resulting in 36 observations. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews 12. The results show that IOS and profitability positively and significantly affect firm value, while firm growth has no significant effect. CSR significantly moderates the relationship between IOS and firm value, but does not moderate the effects of growth and profitability. These findings support signaling and agency theory and highlight that strategic CSR aligned with substantial investment and profit potential can enhance firm value, especially in sharia-based capital markets.